Design and Control of a Low-Cost Ball and Beam Platform for Control System Education - Suarez Ruiz, Rodrigo; Cruz Gonzalez, Enrique Eduardo; Tapia Guerrero, Maria Alexandra; Martinez Escamilla, Juan Guillermo; Pérez Ramírez, David Elim; Espejel Rivera, María Angélica; Hernández Pérez, Javier (International Journal of Combinatorial Optimization Problems and Informatics, 2025)
The Ball & Beam system is one of the most comprehensive case studies in the field of control, as it is naturally unstable. This paper proposes a control approach for the Ball & Beam system composed of a PID controller and a Kalman filter, which are used to estimate system states and mitigate problems caused by the sensor’s high sensitivity to noise. The control is implemented using the Arduino software. Finally, the results of the simulation and implementation show that the control is effective despite the noisy signal, resulting in a low-cost prototype for educational purposes.